2023
DOI: 10.1589/jpts.35.75
|View full text |Cite
|
Sign up to set email alerts
|

Relative and absolute reliability of gait variables obtained from gait analysis with trunk acceleration in community-dwelling individuals with chronic stroke: a pilot study

Abstract: This pilot study aimed to investigate the relative and absolute reliability of variables obtained from an acceleration-based gait analysis conducted at comfortable and maximal gait speeds in individuals with chronic stroke. [Participants and Methods] This study included 25 community-dwelling individuals with chronic stroke. The participants wore triaxial accelerometers, while an observed walking trial was performed at comfortable and maximal speeds on two separate days 1 week apart. Relative reliability was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Patients are assessed twice in a typical test-retest experiment for estimating SEM or the reliability of mobility measures, usually one week (e.g. [ 48 ]). or a couple of weeks apart (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are assessed twice in a typical test-retest experiment for estimating SEM or the reliability of mobility measures, usually one week (e.g. [ 48 ]). or a couple of weeks apart (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is important to note that studies employing conventional steady-state, test-retest experimental designs pointed out the absence of bias for mobility measures between the two assessment sessions. For example, no systematic difference has been found for several gait variables in walking tests in chronic stroke patients [ 48 ]. A bias is not explicitly underlined in a systematic review of the reliability of gait measures [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDC in normalized RMS was higher in ML than in VT and AP. Normalized RMS is widely used to measure trunk sway in the gait assessment of patients with stroke 5,16,[30][31][32] . In addition, the trunk sway obtained by RMS after stroke is significantly different from that of healthy people, allowing for specific gait characteristics after www.nature.com/scientificreports/ stroke 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the measures' MDCs allows discrimination between measurement error and true change, which is a valuable insight in determining the effectiveness of rehabilitation interventions. MDC of trunk acceleration indices has been reported in healthy people 15 and patients with chronic stroke 16,17 . However, the MDC of trunk acceleration indices during walking in inpatients with subacute stroke is yet to be clarified.…”
Section: Minimal Detectable Change In Inertial Measurement Unit-based...mentioning
confidence: 99%
“…The HR has been reported to assess regularity, harmony, and symmetry of movements; discriminate between the gait of younger adults and that of older adults 9) ; and elucidate the fall experience of older adults 10) . In this regard, the reliability and usefulness of HR as an assessment of regularity and asymmetry in gait for unilateral disability after stroke have been reported 11,12) . Furthermore, Wada et al 13) reported that preoperative and postoperative gait evaluation of females with osteoarthritis of the hip joint showed improved HR; however, their HR values were lower than those of healthy participants, suggesting residual asymmetry.…”
Section: Introductionmentioning
confidence: 99%